Dark days, determined people : stories from Ukraine under siege - Hrudka, Orysia; Ben, Bohdan (Ukrainian voices (Stuttgart, Germany), 2024)
When in February 2022 Russia attacked Ukraine full-on from the north, east, and south, a Kyiv Theology Professor joined the Ukrainian defense as a sniper and left the city to fight near Chornobyl. Elsewhere, a small group of Chernihiv residents rescued thousands of locals from the besieged city, using hidden roads to bypass Russian soldiers. Others found themselves under Russian occupation, living in constant fear of Russian soldiers entering their yards. In the midst of war, reality surpasses any fiction. What does the former businessman feel when he evacuates the bodies of fallen soldiers, day after day? Why do some people choose to live in the rubble of their flattened homes? How do Ukrainian soldiers who survive only because of an amputation cope with recovery, and how do Ukrainian rehabilitation specialists cope with the surge of patients? What continues to motivate people to fight who just yesterday didn't believe such a war was possible? These 21 stories, collected from diverse regions of Ukraine since the beginning of the 2022 full-scale invasion, speak of courage, resilience, pain, death, love, and hope.